2017
DOI: 10.1160/th17-02-0085
|View full text |Cite
|
Sign up to set email alerts
|

F7 gene variants modulate protein levels in a large cohort of patients with factor VII deficiency

Abstract: Congenital factor VII (FVII) deficiency is a rare bleeding disorder caused by mutations in F7 gene with autosomal recessive inheritance. A clinical heterogeneity with poor correlation with FVII:C levels has been described. It was the objective of this study to identify genetic defects and to evaluate their relationships with phenotype in a large cohort of patients with FVII:C<50 %. One hundred twenty-three probands were genotyped for F7 mutations and three polymorphic variants and classified according to recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 46 publications
3
39
1
Order By: Relevance
“…Mutations in this domain may severely affect the coagulation activity and the secretion of the FVII protein. However, considerable evidence now supports the concept that there is no clear genotype-phenotype association in FVII deficiency (14). Preceded by several publications based on various mutations, it has been demonstrated that the disease manifestations, including epistaxis, hemarthrosis and menorrhagia, do not always associate with FVII:C (1,15).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this domain may severely affect the coagulation activity and the secretion of the FVII protein. However, considerable evidence now supports the concept that there is no clear genotype-phenotype association in FVII deficiency (14). Preceded by several publications based on various mutations, it has been demonstrated that the disease manifestations, including epistaxis, hemarthrosis and menorrhagia, do not always associate with FVII:C (1,15).…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, intronic variants and epigenetic alterations can play a role in disease pathogenesis, and HTS may be relevant in these cases. 71 The most important findings derived from the molecular data from this study were: (1) patients with at least one variant involving a domain other than the catalytic domain of FVII presented Fig. 4 Genetic variants in the landscape of CalDAG-GEFI: the figures identify the many genetic variants that have been reported in CalDAG-GEFI that impair the function of these proteins and subsequently impair αIIbβ3 activation.…”
Section: Inherited Thrombocytopeniamentioning
confidence: 81%
“…This detected several novel variants, and large deletions (6%), which are rarely reported in F7. 71 An underlying genetic variant was not found in 42% of the patients included. In these cases, intronic variants and epigenetic alterations can play a role in disease pathogenesis, and HTS may be relevant in these cases.…”
Section: Inherited Thrombocytopeniamentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, the affected women often suffer from severe menorrhagia [29] . In sum, FVII deficiency is a rare bleeding disorder with variable clinical symptoms [28][29][30][31][32][33][34][35][36][37] . However, in many cases, there is no direct correlation between the factor plasma levels and the severity of the disease symptoms [28][29][30]32,38] .…”
Section: Factor VII Deficiencymentioning
confidence: 99%